(untitled) (Al-Aasar, 2024)
The rapid advancement of digital technology has significantly transformed the methods used to preserve and document cultural heritage. Many forms of traditional arts, crafts, and cultural expressions are increasingly at risk due to modernization, urbanization, and globalization. Technologies such as Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), and 3D scanning are playing a crucial role in the digital preservation of cultural heritage. This research paper examines how digital transformation can help protect traditional arts, improve documentation, and enhance global accessibility to cultural heritage. The study also highlights how AI-based analytical systems assist in the restoration of historical artworks, pattern recognition, and the automated classification of cultural materials. Furthermore, virtual museums and digital archives provide effective platforms for transmitting cultural heritage to younger generations. The findings indicate that digital technologies are creating new opportunities for the preservation, research, and educational dissemination of cultural heritage.